¿Es relevante la coca? “Narcodólares” y el tipo de cambio real - Cruz-Saco Oyague, María Amparo (1994)
This article examines the hypothesis that the real exchange rate's appreciation in Peru and the export revenues related to the production of coca were strongly associated between 1985- 1990. This theory is based on the supposition that the influence of “narcodollars” caused dollar supply in the free exchange market to skyrocket and forced down the equilibrium price. However, the results of these estimations do not provide enough evidence to support this hypothesis.